Studies on viscosity and conductivity of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU)-glycerol and CO2-DBU-glycerol solutions at temperatures from 288.1 K to 328.1 K. (September 2019) - Liu, Yingying; Lin, Si; Lu, Houfang; Liu, Changjun; Wu, Kejing; Jiang, Wei; Liang, Bin
Highlights: Viscosity and conductivity of DBU-glycerol and CO2 -DBU-glycerol systems were measured. Maximum viscosity and conductivity are at x 1  = 0.2153 and 0.0914 for DBU(1)-glycerol(2) system. Viscosity increases with the content of CO2 in CO2 -DBU-glycerol system when x 1  > 0.2. Conductivity is greatly affected by the composition and temperature. Different models were proposed to correlate the viscosity and conductivity for both systems. Abstract: Solutions of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU)-glycerol are promising chemical absorbents for CO2 removal. Understanding the physicochemical properties of the solution and solution-absorbed CO2 are essential for its applications. The viscosity and electrical conductivity of DBU-glycerol and CO2 -DBU-glycerol solutions were studied using a cone-plate viscometer and a conductivity-measuring instrument, respectively, at temperatures from 288.1 K to 328.1 K. For the DBU-glycerol system, the viscosity decreases with increasing temperature, whereas its conductivity increases. The viscosity and conductivity initially increase with DBU molar fraction ( x 1 ), with maximum viscosity and conductivity observed at x 1  = 0.2153 and 0.0914, respectively. The viscosity and conductivity were calculated using the Redlich-Kister method and Castell-Amis equation, respectively. For the CO2 -DBU-glycerol system, the highest viscosity was 52 times higher than that of DBU-glycerol system when the mass content of CO2 ( ω CO2, based on the total mass of DBU and glycerol) was less than 0.08. However, the conductivity decreased by approximately 70–89% when ω CO2 increased from 0 to 0.0417 for x 1  = 0.1000 or from 0 to 0.0886 for x 1  = 0.2000. But when x 1  = 0.5000, 0.7500 and 0.8333, the conductivity initially increased by 1.4–14 times and subsequently decreased by 6–95% when ω CO2 increased from 0 to 0.1395. Modified viscosity and conductivity models are proposed herein for the CO2 -DBU-glycerol mixtures with average relative deviations of 5.13% and 2.99%, respectively.